Polychromatic adaptation end psychic-physiological status of the man in the Antarctic - Moiseyenko, Y.; Madiar, S.; Kovalevskaja, E. (Ukrainian Antarctic Journal, 2006)
The study of the particularities of the psychic-physiological status, as well of an influence of the polychromatic spectra upon a man while having a long-term stay under the conditions of the monochromatic environment on an Antarctic station has been as an aim of the work.